2016
DOI: 10.1016/j.intmar.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining Biased Assimilation of Brand-related Online Reviews

Abstract: This paper examines the impact of pre-existing brand attitudes on consumer processing of electronic word-of-mouth (eWOM). This topic is particularly important for brands that simultaneously possess strongly pronounced proponents as well as opponents. Two experimental studies using univalent (study 1, N= 538) and mixed (study 2, N= 262) sets of online reviews find indications for biased assimilation effects of eWOM processing. Consumers perceive positive (negative) arguments in online reviews as more (less) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 72 publications
2
29
0
1
Order By: Relevance
“…When eWOM communications are useful they significantly affect an individual's purchase intention (Jeong and Koo 2015). Several studies have investigated the relationship between eWOM usefulness and purchase intention (Cheung 2014;Frasquet et al 2015;Gunawan and Huarng 2015;Huang et al 2013;Lee et al 2011;Mafael et al 2016;Lee 2008, 2009). For example, Huang et al (2013) used data from 549 respondents from China and found that eWOM usefulness positively affects hotel booking intention.…”
Section: Ewom Usefulnessmentioning
confidence: 99%
“…When eWOM communications are useful they significantly affect an individual's purchase intention (Jeong and Koo 2015). Several studies have investigated the relationship between eWOM usefulness and purchase intention (Cheung 2014;Frasquet et al 2015;Gunawan and Huarng 2015;Huang et al 2013;Lee et al 2011;Mafael et al 2016;Lee 2008, 2009). For example, Huang et al (2013) used data from 549 respondents from China and found that eWOM usefulness positively affects hotel booking intention.…”
Section: Ewom Usefulnessmentioning
confidence: 99%
“…Brands in B2C markets not only act as a signal in themselves, but they also impact how consumers respond to unintentional signals, such as social media reviews. Mafael, Gottschalk and Kreis (2016) have found that brand attitude is indeed very important in determining how consumers process eWOM information, so that if they have a positive attitude towards the brand, they find positive arguments in an eWOM review more persuasive and negative arguments less persuasive than if they have a negative attitude towards the brand. Such biased information processing of social media signals would be less likely to occur in B2B markets.…”
Section: Signalling Theory In B2b Marketsmentioning
confidence: 99%
“…An informal communication about various brands takes place among the consumers in the form of online product reviews, where they share their experiences of such brands in various brand communities, brand pages and other online social media platforms (Steinmann, Mau, & Schramm-Klein, 2015; Ziegele & Weber, 2015). Such reviews can influence the consumer’s purchasing decision (Mafael, Gottschalk, & Kreis, 2016). Consumers generally give their opinions on various brands through online reviews, which creates an image of the brand in consumer’s mind (Költringer & Dickinger, 2015).…”
Section: Introductionmentioning
confidence: 99%